1994
DOI: 10.1002/ijc.2910580114
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of ICAM‐1 (CD54) expression in human breast cancer cell lines by interleukin 6 and fibroblast‐derived factors

Abstract: Four human breast cancer cell lines (T47D, ZR-75-1, MCF7D and HS578T) were examined for the effects of cytokines on expression of cell surface antigens. Interferon (IFN)gamma up-regulated the expression of ICAM-I (CD54) in all the cell lines and coordinately up-regulated both CD54 and CD40 expression in T47D. Tumour necrosis factor (TNF)alpha, interleukin (IL)1 alpha, IL1 beta and IL6 also up-regulated the expression of CD54 in all the cell lines but CD40 was unaffected. Levels of expression of CD11a, CD18, CD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
0

Year Published

1996
1996
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(33 citation statements)
references
References 14 publications
2
31
0
Order By: Relevance
“…has also been demonstrated to induce ICAM-1 expression on several types of epithelial tumors including breast carcinomas. 29,30,39 In contrast, VCAM-1 has not been examined with respect to induction with TNF-␣; however, in other studies VCAM-1 has not been shown to be expressed by breast carcinoma cells. 14 RT-PCR, Western blotting, and cell surface ELISAs were used to examine adhesion molecule expression on several breast carcinoma cell lines.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…has also been demonstrated to induce ICAM-1 expression on several types of epithelial tumors including breast carcinomas. 29,30,39 In contrast, VCAM-1 has not been examined with respect to induction with TNF-␣; however, in other studies VCAM-1 has not been shown to be expressed by breast carcinoma cells. 14 RT-PCR, Western blotting, and cell surface ELISAs were used to examine adhesion molecule expression on several breast carcinoma cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…[27][28][29][30] We first used RT-PCR to determine if these cells synthesized mRNA for various adhesion molecules. MDA-MB-435S and MDA-MB-468 cells both constitutively expressed high levels of mRNA for ICAM-1 ( Figure 1A).…”
Section: Expression Of Icam-1 and Vcam-1 Mrna By Breast Carcinoma Celmentioning
confidence: 99%
“…IL6 has also been shown to induce ICAM1 (CD54) expression in carcinoma cell lines (Hutchins and Steel, 1994) and may be part of the mechanisms by which CD40 and LMP1 up-regulate this phenotypic marker. Thus, we have found that treatment of T47D cells which express relatively low levels of ICAM1, with 500 or 1000 pg ml 71 rhIL6 induces a signi®cant increase in ICAM1 levels (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…IL6 is a cytokine with pleiotropic activities and has been shown to play a central role in immune host-defence mechanisms by perpetuating an in¯ammatory response (Akira et al, 1993). Important functions of IL6 include up-regulation of ICAM1 (CD54), an adhesion molecule mediating immune and inflammatory responses (Hutchins and Steel, 1994), induction of di erentiation of certain haemopoietic cell lines and growth inhibition or stimulation depending on the nature of the responsive target cell (Kawano et al, 1988;Chen et al, 1991;Takizawa et al, 1993). IL6 has also been shown to be an important co-stimulatory molecule for primary generation of antitumour cytolytic T lymphocytes in vitro (Gajewski et al, 1995) and an essential co-factor for CD40-induced isotype switching (Jabara et al, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…Constitutive activation of STATs, in particular Stat3, is found in a number of primary human tumors and cancer cell lines (Turkson, 2004), including lung cancer (Fernandes et al, 1999). Interleukin (IL)-6 is a pleiotropic cytokine that not only regulates immune and inflammatory responses but also regulates cell growth in many tumors (Kishimoto et al, 1992;Hutchins and Steel, 1994;Siegsmund et al, 1994;Okamoto et al, 1997). Interleukin-6 is required in the control of cell proliferation in a subset of human NSCLC cell lines (Bihl et al, 1998), because GP130/ JAK/Stat3 is one of the major pathways for mediating IL-6 signaling and IL-6 participates in the upregulation of VEGF via Stat3 activation in cervical cancer cells (Wei et al, 2003).…”
Section: Introductionmentioning
confidence: 99%